Arbejdet som improvement - landbrug, husholdning og kapitalisme i 1500- og 1600-tallets England - Bøgh Sørensen, Esben (Slagmark - Tidsskrift for idéhistorie, 2018)
WORK AS IMPROVEMENT - HUSBANDRY, HOUSEKEEPING AND CAPITALISM IN 16TH ANN 17TH CENTURY ENGLAND This article traces the development of a new attitude to work as improvement in early modern England. By focusing on agricultural manuals from the period, the author shows how the attitude to work as improvement developed as a response by yeomen and gentleman farmers to their increasing subjection to market imperatives. In contrast to the ethics of housekeeping, which stressed the good maintenance and ordering of the ‘house’ in the broadest sense as the primary aim of social and economic activities, the new idea of improvement focused on activities directed at the market. This idea established new distinctions between good and bad work, and it created new criteria for valorizing different types of agricultural activities. The constant drive to measure the value of agricultural work in terms of market price, and to continually raise productivity and efficiency and make use of the latest techniques and inventions became pivotal for these agricultural writers. The idea of work as improvement had a wide range of new moral, cultural and political dimensions, all of which consolidated into a more coherent ideology of improvement by the late 16th century.